A descriptive cross-sectional survey among the International Islamic University Malaysia’s student on e-waste generation and public health problem in Malaysia - Islam, Mohd Aminul; Azad, Abul Kalam; Sunzida, Nushrat Khan (Wolters Kluwer Medknow Publications, 2019)
Objective: The main aim of the survey was to assess the respondent’s opinion on the factors influencing the generation of e-waste and its impact on public health in Malaysia. Methods: The research project involved a cross-sectional survey of International Islamic University’s students conducted in 2017 at Kuantan campus in the Pahang state, Malaysia. Along with info on demographic individualities, data were collected on several factors (agreement with questionnaire items regarding) using a 4-point Likert scale, with 4 representing “agree”, “strongly agree”, “disagree” and “strongly disagree,” respectively. Results: A total of 296 students completed the questionnaire. The age group of 18-22 covers 46.96% of all respondents and 61.82% was females. In ethnicity of respondents, 86.82% Malay and 30.07% were from rural area and rest of them were urban area. The volume of e-waste is raised due to the excess supplies of electrical appliances (71%), update their devices (65%.), additional electrical devices (59%), keeping the unused electrical appliances (71%), wholesalers selling bad quality appliances (45%), mechanic should not add and drop of their devices (71%). Regrettably 83% of the respondents doesn’t have appropriate knowledge of e-waste. 51% students agreed and 38% strongly agreed that there is no noticeable campaign on e-waste for public awareness. According to the 93% students’ opinion, individuals, the suppliers, industries and even the institutions are not aware to reduce e-waste. But a little 20% think that government does provide facilities for electrical device disposal. In public health perspective, e-waste contains a lot of hazardous chemical (strongly agreed 77% and rest 23% agreed). Fortunately, the serious health hazards led by e-waste (86% strongly agreed and 14% agreed). E-waste leads to infertile land, cancer, lung diseases and so others strongly agreed 70% and agreed 22% respectively. Conclusion: Findings suggest to organize the awareness programme in institutional, organization and educational institutional level to reduce generation of e-waste and its risk.